Perspektif Mahasiswa PGMI Terhadap Tujuan dan Materi Pembelajaran dalam Pendidikan Humanis - Miftha Huljannah; Maryam Rahim; Mohamad Zubaidi (TA'DIBAN, 2026)
This study aims to describe PGMI students’ views on learning objectives, learning materials, and the relationship between the two within the perspective of humanistic education. The study employed a descriptive quantitative approach. The sample consisted of 40 PGMI students at IAIN Sultan Amai Gorontalo selected through purposive sampling. The research instrument was a 24-item questionnaire that had been tested for validity and reliability. The data were analyzed using descriptive quantitative analysis with percentages. The findings showed that PGMI students’ views on learning objectives were in the very good category, with a percentage of 86.2%, while their views on learning materials were also in the very good category, with a percentage of 86.82%. In addition, PGMI students demonstrated a very good level of understanding regarding the relationship between learning objectives and learning materials within the perspective of humanistic education. These findings indicate that PGMI students have a very good understanding of the importance of learning objectives and learning materials that humanize learners.